Triangulating Timbre in Sigur Rós's Iceland ... - Blake, David K.; Osborn, Brad (Humanities Commons, 2019)
Osborn, Brad and D.K. Blake. 2019. “Triangulating Timbre in Sigur Rós’s Iceland.” In *Sounds Icelandic*, edited by Thorbjörg Daphne Hall, N. Dibben, Á.H. Ingólfsson, and T. Mitchell. Equinox Press, 208–219. ...